Investigation of neighbour group effects in releasing of 5-aminosicylic acid from acrylic polymeric prodrugs - Babzadeh, Mirzaagha; Naserian, Sona (Видавництво Львівської політехніки, 2011)
Acrylic-type polymeric systems having degradable ester bonds linked to 5-ASA were synthesized and evaluated az materials for drug delivery. prodrugs. 5-aminosalicylic acid (5-ASA) was linked to 2-hydroxypropyl methacrylate by carbonyldiimidazole (CDI) to obtain metachryloyloxy propyl 5-amino salicylate. The resulting acrylic derivative of 5-ASA was copolymerized with 2-hydroxyethyl methacrylat, methyl metacrylat and 2-ethylh hexyl acrylate (in 1:3 mole ratio) by free radical polymerization method in N,N-dimethyl formamid solution, utilizing benzoyl peroxide as an initiator at 70 °C. The obtained polymer was characterized by FT-IR .Gel permeation chromatography was used for determination of average molecular weights of polymers bearing drug units as side substituents of the acrylic backbone. Release studies of 5-ASA were performed into dialysis bags by hydrolysis buffered solutions (pH 1, 7.4, 10) at 37 ºC . Detection of hydrolysis by UV spectroscopy at selected interval showed that the drug can be released by selective hydrolysis of the ester bond at the side of drug moiety. The release profiles indicated that the hydrolytic behavior of polymeric prodrugs is strongly based on the hydrophobicity of polymer and the pH of the hydrolysis solution.
Keywords: 5-aminoslicylic acid; polymeric prodrug; acrylic polymeric; 2-hydroxypropyl methacrylate